Preparing Future Teachers for Enrichment as Curriculum: A Candidate Preparation Sequence - Emily George; Joan Sinagra Brillant (The Advocate, 2026)
This paper explores the importance of ensuring teacher preparation programs equip teacher candidates with the knowledge, dispositions, and tools necessary to differentiate instruction and provide enrichment opportunities that engage and challenge all learners, not just those students identified as advanced or gifted. Grounded in research on equity, motivation, and access to rigorous learning, the paper argues that enrichment should be treated as a curriculum norm rather than an add-on or reward. The authors propose a candidate preparation sequence of awareness, stance, practice, and implementation to help future teachers build inclusive classrooms where challenge, support, agency, and opportunity coexist.
Keywords: enrichment; teacher education; teacher candidates; gifted education; self-determination theory; engagement; motivation; curriculum